Analisis Aspek Kesulitan Membaca Awal Pada Siswa Kelas Satu Di Sekolah Dasar Kota Semarang - Subagyo, Norita Agustina (Universitas Pahlawan Tuanku Tambusai, 2024)
Early reading skills in some primary school students still face various difficulties. These challenges are often not detected early on, so they can develop and hinder their learning process. This study aims to analyze the early reading difficulties experienced by grade 1 students at SD Negeri Ngijo 1. The research was conducted with a descriptive qualitative approach, using data collection techniques in the form of observation, interviews, and documentation. Data validity was strengthened through the triangulation method. The data analysis process includes data collection, reduction, presentation, and conclusion drawing. The results showed that the highest difficulty in early reading was in digraph letter recognition experienced by 19 students. Other difficulties include word recognition (16 students), word stringing (13 students), consonant letter recognition (11 students), letter identification in words (4 students), and vowel letter recognition (3 students). The habit of learning to read must be applied more in school and home learning with learning methods and strategies that adjust to individual needs.